Characteristics of Adolescent Diversity in Islamic Perspective - Zakaria, Zuraida; Maryana, Maryana; Widari, Lis Ayu; Ilyas, Mukhlisuddin; M, Munawar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2024)
This study aims to find out in Islam, there is no separate discipline from Islamic ethics. As a business that is identical with religious teachings, religious characters in Islam are unique and different from characters outside of Islam. These differences include an emphasis on eternal religious principles, rules and laws in strengthening morality, differences in understanding of the truth, and an emphasis on reward in the afterlife as a motivation for moral behavior. The basis of character formation is good or bad values. Good values ??are symbolized by the value of Angels and bad values ??are symbolized by the value of Satan. Human character is the result of attraction between good values ??in the form of positive energy and bad values ??in the form of negative energy. research originating from books, scientific journals, literatures and other publications that are worthy of being used as sources for research to be studied by the author, by describing and describing the data through several expert opinions.